Factors Affecting QR Code Usage in Nepal (Global Journal of Management and Business Research, 2023)
Quick Response QR codes are two-dimensional and machine-readable matrix bar codes created by Hara Masahiro an engineer for Denso Wave Incorporated a Toyota subsidiary in 1994 for accurate and fast inventory checks QR-code was first used in Japan s Kanban a type of electronic communication tool used in the automotive industry Stein 2020 QR code was used in manufacturing and expanded to the logistics and retailing industry In the marketing field QR-code had been used widely to understand consumer behavior market research retailing and marketing communication Tolliver-Walker 2011